Prensa sensacionalista caso Diario Extra y su impacto deontológico en los lectores adultos de sexo masculino de la Parroquia Venus Cantón Quevedo - Meza Carreño, Nataly Marianita (2019)
The purpose of this investigation is to determine the deontological impact of the sensational press newspaper, Diario Extra, which is directed and focused on adult male readers of the Venus parish, of the Quevedo city. Through the application of surveys, it was determined that this medium uses sensationalismas a journalistic style for the attraction and conservation of its consumers. For the solution of the problem, a training of the codes and deontological norms established in articles 9 and 10 of the Organic Law of Communication was developed. A previous interview was conducted to obtain a professional opinion of the importance of these codes in media outlet. The study was based on scientific texts and documents related to the subject, for the argument of the theoretical, legal, historical and sociological foundations, which gave the conceptualizations, causes, consequences, factors that determine the impact that this means of communication has on its readers.